The Comparison of Self-Control and Experimental-Control Feedback Frequencies on Learning a Throwing Task in Children with Cerebral Palsy - Morteza Pourazar; Rasool Hemayattalab; Elahe Arabameri (رشد و یادگیری حرکتی ورزشی, 2014)
Cerebral palsy is a term commonly used for conditions characterized by motor dysfunction due to non-progressive brain damage in early life. The aim of this study was to compare the effects of self-control and experimental-control feedback frequencies on the acquisition, retention and transfer of a throwing task in children with spastic cerebral palsy. From 1750 students with cerebral palsy in Tehran special schools, 30 children (7-12 years old) with spastic hemiplegic cerebral palsy (SHCP) were selected by a convenience sampling method. A pretest consisting of 10 trials was performed to homogenize the participants. Participants were randomly divided into three self-control groups (with 25%, 50% and 75% feedback frequencies) and three experimental-control groups (with 25%, 50% and 75% feedback frequencies) in acquisition, retention, and transfer phases. In the acquisition phase, subjects completed 10 blocks of 8 trials (total of 80 trials). Retention and transfer phases were conducted 24 hours after the acquisition phase. These phases consisted of 10 trials without feedback, except that the subjects performed the transfer phase from 4m distance (vs. 3m distance in acquisition and retention phases). One-way ANOVA test showed no significant difference between the groups receiving the same frequencies (self-control and experimental-control groups) in the acquisition phase while self-control group outperformed in retention and transfer phases. Furthermore, participants who received higher feedback frequencies (self-control or experimental-control group) outperformed those in lower feedback frequencies in all acquisition, retention, and transfer phases. Thus, while the advantages of self-control feedback against experimental-control feedback were observed in the same feedback frequencies, it seems that children use feedbacks in a manner different from adults during motor learning. Thus children may require higher feedback frequencies than adults in order to optimize their motor learning.